Students Perceived Usefulness and Ease of Use on Quizizz in EFL Classroom - Ariyanti, Septika; Mulati, Dyah Fitri; Inawati, Iin (SCOPE: Journal of English Language Teaching, 2025)
An educational portal called Quizizz provides a variety of resources to enhance student engagement and make studying enjoyable. The research objective was to identify (1) students' perceptions regarding the usefulness of the Quizizz learning media applied in the EFL Classroom, (2) students' perceptions regarding the ease of use of the Quizizz learning media applied in the EFL Classroom. This research uses a quantitative method with a statistical descriptive approach which aims to determine students' perceptions regarding the use of Quizizz learning media which is often used during the teaching and learning process. The sample in this study was Pharmacy Study Program students who took the English 2 course, with a total of 52 participants. This class was chosen because it uses Quizizz learning media more in its learning process. In collecting data, a questionnaire consisting of 10 questions with 5 Likert scales will be used in this research. The result showed that the students have good perception in accepting the use of Quizizz especially in perceived usefulness and perceived ease of use. Researchers hope that this research will be useful for both teachers and students, namely to create a more conducive learning atmosphere following technological developments without ignoring the principles of usability and ease of use of this technology. The findings of this study hold significant implications for educators, policymakers, and instructional designers in EFL (English as a Foreign Language) classrooms. By examining students' perceived usefulness and ease of use regarding Quizizz, several key insights emerge that can inform teaching practices and the integration of digital tools into language learning environments